BIOPHYSICAL AND IMMUNOLOGICAL CHARACTERIZATION OF CARBAMYLATED-DNA: SERUM AUTOANTIBODIES OF DIABETIC NEPHROPATHY PATIENTS EXHIBIT STRONG BINDING WITH CARBAMYLATED-DNA (Applied Biological Research, 2023)
Isocyanates (ICN) have drawn considerable attention in recent past as they  can react with a variety of nucleophiles including DNA, proteins and cause  damage(s). However, pathophysiological implications resulting from the  occupational and accidental exposures of ICN are yet too elusive. It may be  produced in high concentrations in the conditions of chronic renal failure  and chronic inflammatory diseases (diabetes mellitus, rheumatoid  arthritis, etc.). In this study, mammalian dsDNA was modified with ICN  and characterized by UV, fluorescence, FT-IR and thermal melting methods. ICN mainly reacts with exocyclic nitrogen of DNA bases.  Antibodies against carbamylated-DNA were raised in rabbits and  characterized by direct binding and inhibition ELISA. The presence of  anti-carbamylated-DNA autoantibodies in the sera of diabetic nephro pathy patients was evaluated by ELISA. Carbamylated-DNA exhibited  hyperchromicity at 260 nm and depicted increase in ethidium bromide assisted fluorescence as compared to the native DNA. Furthermore, the appearance of prominent new peaks in FT-IR profile at different wave  numbers suggested carbamoylation-induced changes in the vibration of  sugar-phosphate backbone, base(s) etc. Carbamylated-DNA was highly  immunogenic as compared to the native DNA. Experimental induction of  antibodies against carbamylated-DNAand presence of autoantibodies  against carbamylated-DNA in the sera of diabetic nephropathic patients  point towards the significance of carbamylated-DNA in diabetic  nephropathy.
Keywords: Autoantibodies; carbamylated-DNA; diabetic nephropathy; isocyanates